Design of filler and compactor for oyster mushroom growing medium (baglog). (May 2019) - Rizaldi, T; Raju,; Piliang, M R
Abstract: Oyster mushroom cultivation requires good quality growing medium (baglog). In addition to good baglog material, a suitable density level is needed for mushroom growth. Filling and compaction of baglog is often found use manual methods so it takes longer time. The objective of this study is to design a filler and compactor mechanical device for mushroom growing medium. The design obtained dimensions of length 150 cm, width 90 cm and height 153.06 cm. The device is operated by an electric motor of 1 Hp with rotation of 1450 rpm. The device capacity is 180 baglog/hour. The design test showed that the material for the main frame component consist of angle bar with size of 40 mm x 40 mm and thickness of 4 mm, was able to load the device with minimum safety factor of 3.58.